2007
DOI: 10.1017/s1461145707008061
|View full text |Cite
|
Sign up to set email alerts
|

Agonist and antagonist properties of antipsychotics at human dopamine D4.4 receptors: G-protein activation and K+ channel modulation in transfected cells

Abstract: Interaction at dopamine D4 receptors may improve cognitive function, which is highly impaired in individuals with schizophrenia, but comparative studies of recent antipsychotics in cellular models of D4 receptor activation are lacking. Here, we report the in-vitro profile of over 30 ligands at recombinant hD4.4 receptors. In [35S]GTPgammaS binding experiments using membranes of CHO-hD4.4 cells, apomorphine, preclamol and the selective D4 agonists, ABT724, CP226269, Ro-10-5824 and PD168077, behaved as partial a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 67 publications
(74 reference statements)
1
14
0
1
Order By: Relevance
“…Furthermore, the functional properties of L750,667, PNU101,387G, ABT-724, and Ro10-5824 for the mutant receptors were the same as for the wild-type receptors: they were all antagonists because they did not activate the receptors and prevented activation by the agonist (Ϫ)-quinpirole. Two of the D4-selective ligands used in this study, ABT-724 and Ro10-5824, have been reported to possess partial agonist properties when using either [ 35 S]GTP␥S binding or FLIPR assays as functional end points (Powell et al, 2003;Cowart et al, 2004;Newman-Tancredi et al, 2008). However, using intracellular cAMP accumulation as a functional endpoint we found that ABT-724 and Ro10-5824 lacked agonist properties, but antagonized (Ϫ)-quinpirole activation in wild-type and mutant receptors.…”
Section: Resultsmentioning
confidence: 61%
“…Furthermore, the functional properties of L750,667, PNU101,387G, ABT-724, and Ro10-5824 for the mutant receptors were the same as for the wild-type receptors: they were all antagonists because they did not activate the receptors and prevented activation by the agonist (Ϫ)-quinpirole. Two of the D4-selective ligands used in this study, ABT-724 and Ro10-5824, have been reported to possess partial agonist properties when using either [ 35 S]GTP␥S binding or FLIPR assays as functional end points (Powell et al, 2003;Cowart et al, 2004;Newman-Tancredi et al, 2008). However, using intracellular cAMP accumulation as a functional endpoint we found that ABT-724 and Ro10-5824 lacked agonist properties, but antagonized (Ϫ)-quinpirole activation in wild-type and mutant receptors.…”
Section: Resultsmentioning
confidence: 61%
“…On the other hand, apomorphine modified also other copulatory parameters, e.g. it decreased EL and IF, which were not affected by (e.g., a measure of the activation of G-protein coupled receptors after receptor binding, which is used to study the activation of D 4 receptors Newman-Tancredi et al 2008], and 2) the EC50 of apomorphine (4.3 nM) is lower than that of PD-168,077 (5,6 nM) and of ABT-724 (12,4 nM) in increasing Ca 2+ influx in HEK-293 cells co-transfected with rat/human D 4 receptors and a G protein (Gαq05) (see [Brioni and Moreland, 2006] and references therein). Alternatively, PD-168,077 and ABT-724 may act as dopamine D 4 receptor partial agonists, or the concomitant activation of different dopamine receptor subtypes by apomorphine may produce a higher activation of the targets (see below), which lead to copulation, than the activation of one dopamine receptor subtype only.…”
Section: Accepted Manuscriptmentioning
confidence: 96%
“…These include 5‐HT 2C receptors (antagonistic action), 5‐HT 2B receptors (antagonistic action) (Tables 1 and 2), and DA D4 receptors. For the latter, flibanserin acts as either an antagonist or a weak agonist, depending on the model system used for testing ([18,32,33]; data on file) (Table 2). Affinity of flibanserin for numerous other receptors is low (Tables 3 and 4; Figure 2).…”
Section: Multifunctional Binding Properties: Flibanserin Is a 5‐ht1a mentioning
confidence: 99%